Mixotrophy in Chlorella sorokiniana : physiology, biotechnological potential and ecotoxicology - Marchello, Adriano Evandir (Universidade Federal de São Carlos, 2017)
In aquatic environments, phytoplankton consists mostly of photosynthetic microorganisms that serve as the basis of food chains. However, besides photoautotrophy, it is widely reported in the literature that many microalgae can take up dissolved organic matter present in the environment concomitantly with the photosynthesis, a metabolic pathway known as mixotrophy. Little is known about the ecophysiology of mixotrophy in microalgae, and almost all studies are focused on the use of this metabolic pathway to increase the production of algal biomass and stimulate the production of specific biomolecules. Another important issue, considering the current anthropic activity, is that most of the contaminants eliminated in aquatic environments, such as metals and nanoparticles, affect the phytoplankton. However, so far, no ecotoxicological study involving mixotrophic metabolism was found in the literature. To better understand mixotrophy in microalgae, this work chose the chlorophycean freshwater Chlorella sorokiniana as test organism. We divided the study into two parts: the first focused on the physiological/biotechnological interest through the study of growth, photosynthetic parameters, changes in cellular volume, and production of biomolecules (proteins, carbohydrates and lipids); the second part focused on the ecotoxicological effects of cadmium (Cd) and titanium dioxide nanoparticles (NPs-TiO2). To stimulate mixotrophy, glucose (1.0 g.L-1 or 5 x 10-3 mol.L-1) was used as the organic carbon source. The results showed that during mixotrophy, the microalga C. sorokiniana presented higher population growth and production of biomolecules, such as chlorophyll a and lipids, when compared to photoautotrophic cultures. It was also observed that the photosynthetic parameters were affected by mixotrophy, although they did not interfere in the growth of the microalga, and that the presence of bacteria in the cultures acted as a stimulant factor in the production of algal biomass. Regarding the ecotoxicological effects of contaminants, microalgae in mixotrophy were more resistant to both Cd and NPs-TiO2 than those in photoautotrophy, but with changes in the biochemical composition what can affected the energy transfer in the environment. In general, we can conclude that mixotrophy should be considered in studies with phytoplankton, since aquatic environments present a myriad of organic carbon that can be used by these microorganisms. As general conclusions, we can mention that organic carbon acted as an extra source of structural carbon and energy for microalgae, not necessarily relying solely on photosynthesis to survive, so stimulating the growth and production of biomolecules of biotechnological interest, and increased cellular viability in environments contaminated with metals and nanoparticles. This study is a contribution to the understanding of mixotrophy and photoautotrophy metabolisms in a freshwater Chlorophyta with biotechnological potential.
Keywords: Mixotrofia; Produção de biomassa; Lipídeos; Cádmio; Nanopartículas; Mixotrophy; Biomass production; Lipids; Cadmium; Nanoparticles; CIENCIAS BIOLOGICAS::ECOLOGIA